Exploring the Levels and Dimensions of Foreign Language Anxiety (FLA) in English Classrooms: A Study on Vocational High School Students - Abdullah Kafabih; M. Nuril Anwar Habiby; Habsah, Ilvia (General English Education, 2026)
This study explores the levels and dimensions of foreign language anxiety (FLA) among vocational high school (VHC) students in Gresik, Indonesia, consisting on communication apprehension, test anxiety, and fear of negative evaluation. Utilizing a quantitative descriptive survey design, data were collected from 220 students using the FLCAS. The findings indicate a moderate overall level of FLA (M = 3.08), with fear of negative evaluation being the most prominent dimension (M = 3.19), suggesting that students are particularly concerned about being judged by peers and teachers when using English. Communication apprehension (M = 3.06) and test anxiety (M = 3.03) also contribute to students' anxiety levels, impacting their engagement and performance in English learning. The study highlights the need for pedagogical strategies that address these anxiety dimensions, such as fostering a supportive classroom environment, implementing collaborative learning, and utilizing alternative assessment methods. These findings underscore the importance of understanding the emotional factors influencing language learning, particularly in vocational education contexts, and call for further research to explore diverse student experiences and employ mixed-methods approaches.